Impact of Infectious Disease Consultation on Clinical Management and Mortality in Patients With Candidemia. (3rd October 2018) - Lee, Rachael A; Zurko, Joanna C; Camins, Bernard C; Griffin, Russell L; Rodriguez, J Martin; McCarty, Todd P; Magadia, Justine; Pappas, Peter G
Abstract: Candidemia has a high attributable mortality. The objective of this study was to determine the impact of infectious disease consultation on mortality and clinical outcomes in candidemia. Infectious disease consultation was associated with better adherence to guidelines and improved survival, even in patients with high Acute Physiology and Chronic Health Evaluation II scores.